PEMANFAATAN BARANG DALAM PERJANJIAN GADAI STUDI KOMPARATIF ANTARA SYAFI’IYAH DAN MALIKIYAH - Husnul Khotimah (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2022)
Pawn is a contract that is allowed in islam and is a detention of an object that is used as collateral for a certain period of time to pay off the debt in whole or in part. In detention, scuh as taking the benefits of pawned goods, according to the malikiyah opinion, those who are entiled to take the benefis of pawned goods are murtahin (pawn recipients) on condition that they get permission from rahin and are included in the sale and purchase contract or exchange contract (al mu’aawadhah) with clear terms of time limit. Specified, while according to syafi’iyah, the benefit of the pawned goods is carried out by the rahin (the pawnbroker) as long as it does not reduce the value of the pawned goods. This study aims to discuss the differences of opinion on the use of pawned goods according to syafi’iyah and malikiyah.